X type zeolitic materials synthesized from fly ash using hydrothermal and low-temperature methods - Wojciech Franus (Budownictwo i Architektura, 2010)
This study presents the results of experiments dealing with the possibility of transforming F class fly ash into a zeolitic material. Two types of synthesis methods were used in the research: hydrothermal and low-temperature synthesis. As a result of alkaline reaction of fly ash with NaOH, all experimental cases yielded zeolitic material which is rich in Na-X phase. The mineralogical composition as well as the physico-chemical properties in Na-X phase was obtained. The mineralogical composition as well as the physico-chemical properties of the obtained material are explored and the feasibility of practical application is shown.